Sarcopenia and inflammaging; the effects of functional foodsfor promoting healthy aging - Vasto, Sonya; Vasto, Sonya; Rosa, Luigi Di; Sabatino, Leo; Baldassano, Sara (Norsk tidsskrift for ernæring, 2024)
Background and objectives: Sarcopenia is a disorder characterized by a generalized reduction in muscle mass and strength and related to important negative clinical outcomes, with a series of economic and social implications, including impaired mobility, loss of quality of life, hospitalization and death. Inflammaging is a state of low-grade systemic inflammation which plays an important role in age-related diseases as sarcopenia. Sarcopenia is also linked to chronic diseases such as obesity, diabetes, and metabolic syndrome. Therefore, sarcopenia markers, are urgently needed especially related to musculoskeletal, hormonal, and biochemical status. Several papers agreed on evaluating anthropometric and hormonal markers including cortisol, inflammatory markers including C-reactive protein (CRP) and interleukin-6 (IL-6), and vitamin D concentration. The present study discusses whether, in the nutritional context, supplementation with brown algae of the Ecklonia species enriched functional foods can improve the condition of inflammation and sarcopenia in old cohort study. Methods: We have conducted a blindly, against pacebo, nutritional intervention for four weeks on a court of 48 volunteer subjects (aged spanned between 60 to 75 years old) divided into two experimental groups. Control lettuce group and lettuce group biostimulated with Ecklonia species brown seaweed. The subjects consumed 100 grams of lettuce with or without biostimulation with Ecklonia species brown seaweed for 4 weeks. Blood samples and anthropometric and nutritional analysis were conducted at the beginning of recruitment and after 4 weeks. Results: The results showed changes in biochemical and anthropometric markers of sarcopenia. Subjects who consumed for four weeks biostimulated with Ecklonia species brown seaweed lettuce showed a reduction in levels of cortisol, inflammatory biomarkers such as c-reactive protein (CRP) and IL-6. With respect to vitamin D, the biostimulated with Ecklonia species brown seaweed cohort showed increase concentration after four weeks. Anthropometric analysis showed increase in muscle mass and decrease in fat mass. Discussion: These preliminary data suggest that brown seaweed supplementation enriched functional foods may be a functional choice that can be proposed to improve sarcopenia associated with aging and perhaps age associated disease.